Pelaksanaan Pembebanan Hak Tanggungan Terhadap Hak Guna Usaha Atas Tanah Dalam Perjanjian Kredit bank - Kaesnuari, Fire; , Septarina Budiwati, S.H., M.H (2017)
This research is intended to recognize some steps in the execution of charge Mortgage Right toward The Right to Cultivate upon Land in the term of Bank Credit Agreement as directed in the UU No 4 1996 about Mortgage. The first step is the giving of Mortgage by publishing Mortgage Deed in front of The Land Deed Official with the present of at least two witnessesas the mechanism for fulfilling The Specialty Principle. The second step is the Registration of Mortgage which is done through Indonesian National Land Authority in Sukoharjo Regency by publishing the Certificate of Mortgage as the mechanism for fulfilling The Publicity Principle in Charge Mortgage. The methodology used in this research is the Juridical-empirical Methodology. The research category used is Descriptive Research. The sources used are primary and secondary sources. The data collecting used is through observation, interview, and literary study which then being analized by using the normative-qualitative mehodology. Keywords: Credit Agreement, Mortgage Deed, Certificate of Mortgage Right